Field verification of stream-aquifer interactions: Colorado School of Mines survey field, Golden, Colorado - Poeter, Eileen P., author; Anderman, Evan R., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1993)
The nature of stream/aquifer interactions is determined in a field study on a stream at the Colorado School of Mines survey field in Golden, Colorado. The study measured the temporal and spatial variability during the spring and summer of 1992 of hydraulic parameters controlling stream/aquifer interactions at the streambed level of detail. Included is the determination of the shallow hydraulic gradient directly beneath the stream; measurement using established piesometers and an air permeameter; and, characterization of the streambed. The area was monitored during a variety of conditions. A number of conclusions are drawn regarding the nature of stream/aquifer interactions at the site. The duration of groundwater was found to depend on the amount of precipitation in the area. The response of the groundwater system to precipitation is on the order of days, while the responses to changes in stream stage is almost immediate. The shallow groundwater gradients calculated form the water level data indicates the presence of two groundwater discharge zones at the site. The total reach of stream is generally gaining water form the groundwater system. The range of stream flow velocities observed is fairly uniform and sufficient to transport unconsolidated sediments up to 2 mm in diameter. The grain size distribution was analyzed.
June 1993.
Keywords: Stream measurements -- Colorado -- Golden; Groundwater flow -- Colorado -- Golden; Seepage